Measuring information systems delivery quality - Duggan, Evan W. (Idea Group Pub., 2006)
At present there is neither a commonly-accepted definition of quality for information systems. This collection starts from the idea that improving objective knowledge of potentially quality-enhancing methods is more likely to assist the production of high-quality software than merely experimenting with new gadgets. Topics include a survey of information systems quality concepts and management issues, different views on software quality, making real progress with the Requirements Defects programs, the development of user-driven scenarios, process contributions to IS quality such as using agile methods in systems development, managing risks using action research methods and remodeling paradigms, and quality issues in under-researched areas such as government settings and open source processes.